São José dos Campos e das vocações: uma análise do ideário empreendedor como projeto de competitividade urbana a partir da década de 1990 - Machado, Pedro Henrique Faria (2019)
This research investigates the scope and limits of entrepreneurial ideas in the city of São José dos Campos, as a project of urban competitiveness aimed at attracting better investments to the city. From a cut between 1990 and 2010, we searched for documentary and bibliographical sources, especially in the special anniversary notebooks of the city of São José dos Campos, produced by the region's largest circulation newspaper, Vale Paraibano, actions and strategies discursive models of city governance in order to increase the collective symbolic capital quotient around a distinctive brand for the city from a supposed "entrepreneurial vocation." These efforts, under strong influence of strategic urban planning of Catalan origin, occurred in a context of unfolding economic crisis experienced in the country in the 1980s, reflecting high unemployment in the industrial sector of the city. It is not, however, the first vocation alleged to the city with a view to finding economic alternatives or overcoming financial crises. In the first half of the twentieth century, despite the lack of consensus regarding the climate and the known impurity of its waters, through the efforts of local doctors in divulging the "good qualities" of the city, São José dos Campos becomes a Climate Office Hidromineral, consolidating the city's "sanatorium vocation" as an alternative to local economic development. In the second half of the 20th century, with the advent of penicillin and the treatment of tuberculosis, the installation of the Aeronautical Technical Center (CTA), the inauguration of the Presidente Dutra Highway and, later, the installation of the Aeronáutica S / A. (EMBRAER) and the National Institute for Space Research (INPE), there is an effort by local government to publicize the city's "industrial vocation", considerably increasing its industrial park. The productive restructuring that took place since the 1990s, mainly in the city's military and aeronautical sector, results in a large number of layoffs in the industrial sector, including EMBRAER, which has one of the main symbols of the "industrial vocation". We argue that the local governance effort to create an "entrepreneurial vocation" for the city was based on two central and articulated ideas: that "the city is entrepreneurial" and that "Joseense is an entrepreneur", seeking not to only to increase urban competitiveness, but to make entrepreneurship a recognized brand of the city in a "city market". If the various actions carried out in the city corroborate with the first idea, the same can not be said of the second. In this sense, São José dos Campos presents entrepreneurship rates lower than those of the state of São Paulo, the Metropolitan Region of the Paraíba Valley and the North Coast and, depending on the metric, of Brazil. Such an argument, which values the initiatory self and places the subjects as the main responsible for their employment, in turn, plays a fundamental role as an element of cohesion around the same city project and its unfolding